Studi Pengaruh Suhu Pemrosesan Terhadap Kekuatan Tarik Bioplastik PLA (Polylactic Acid) dan Tepung Kulit Singkong - Ashrori, Moch. Kharis; Puspitasari, Dewi; Ganda, Andita Nataria Fitri (Universitas Negeri Surabaya, 2026)
Conventional plastics are widely used due to their good mechanical properties; however, they pose serious environmental problems because they are difficult to degrade naturally. Therefore, bioplastics based on renewable resources, such as Polylactic Acid (PLA) reinforced with cassava peel flour as a natural filler, have been developed as an environmentally friendly alternative. This study aimed to analyze the effect of processing temperature variations on the mechanical properties and biodegradation rate of PLA–cassava peel flour bioplastics. An experimental method was employed with processing temperatures of 200 °C, 225 °C, and 250 °C. The material composition consisted of 70 wt% PLA and 30 wt% cassava peel flour, which was processed using injection molding through the melt intercalation technique. Tensile test specimens were prepared according to ASTM D638 Type I standards. Mechanical characterization was conducted using a Universal Testing Machine (UTM), while biodegradation behavior was evaluated using the soil burial test for four weeks. The results showed that a processing temperature of 225 °C produced the highest tensile strength of approximately 67 MPa. Increasing the temperature to 250 °C resulted in a decrease in tensile strength and elongation due to thermal degradation, although the elastic modulus and biodegradation rate increased. These findings indicate that processing temperature plays a crucial role in controlling the relationship between processing conditions, material structure, and mechanical properties of PLA–cassava peel flour bioplastic. Keywords: Bioplastic, Polylactic Acid, Cassava Peel Flour, Processing Temperature, Tensile Properties.